Superiority of dutasteride 0.5 mg and tamsulosin 0.2 mg for the treatment of moderate‐to‐severe benign prostatic hyperplasia in Asian men. (9th September 2018) - Haque, Nazneen; Masumori, Naoya; Sakamoto, Sadaaki; Ye, Zhangqun; Yoon, Sang‐Jin; Kuo, Hann‐Chorng; Brotherton, Betsy; Wilson, Timothy; Muganurmath, Chandra; McLaughlin, Megan; Manyak, Michael
Abstract : Objectives: To assess the effectiveness and safety of dutasteride 0.5 mg + tamsulosin 0.2 mg combination compared with tamsulosin 0.2 mg in Asian men with moderate‐to‐severe benign prostatic hyperplasia. Methods: A 4‐week, single‐blind, placebo, run‐in was followed by a 2‐year double‐blind randomized controlled trial in men age ≥50 years with symptomatic benign prostatic hyperplasia, International Prostate Symptom Score ≥12, prostate volume ≥30 cc, prostate‐specific antigen ≥1.5 and ≤10 ng/mL, peak urinary flow >5 and ≤15 mL/s, and voided volume of ≥125 mL. Participants were randomized to oral daily dutasteride 0.5 mg + tamsulosin 0.2 mg combination or tamsulosin 0.2 mg. The primary efficacy end‐point was change in International Prostate Symptom Score at year 2. Results: Data from 607 participants showed a significant reduction in International Prostate Symptom Score ( P < 0.05) at month 24, along with greater improvements ( P ≤ 0.006) in peak urinary flow at every assessment and significant prostate volume reduction at months 12 and 24 ( P < 0.001) in the combination group. Combination therapy was associated with a significant reduction in the risk of acute urinary retention or benign prostatic hyperplasia‐related surgery ( P = 0.012), primarily due to a significant reduction in the risk of acute urinary retention ( P = 0.005). The safety and tolerability profile of combination therapy was consistent with the known profiles for the individual monotherapies. Conclusions: Dutasteride 0.5 mg + tamsulosin 0.2 mg combination therapy showed better clinical outcomes than tamsulosin 0.2 mg monotherapy, making it an effective and safe treatment option for Asian men with moderate‐to‐severe benign prostatic hyperplasia.